2008
DOI: 10.1016/j.cca.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

False positive acetaminophen concentrations in patients with liver injury

Abstract: False positive acetaminophen tests may result when enzymatic-colorimetric assays are used, most commonly with bilirubin concentrations >10 mg/dl, leading to potential clinical errors in this setting. Bilirubin (or possibly other substances in acute liver failure sera) appears to affect the reliable measurement of acetaminophen, particularly with enzymatic-colorimetric assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…[42]). However, other studies seeking to detect evidence for additive effects of APAP use on liver injury during acute viral hepatitis or other causes of liver injury have instead found that some bioanalytical methods for the detection of APAP yield high rates of false positives in the presence of high bilirubin levels and thus may have resulted in overestimation of APAP use during acute liver disease in some studies [43]. …”
Section: Discussionmentioning
confidence: 99%
“…[42]). However, other studies seeking to detect evidence for additive effects of APAP use on liver injury during acute viral hepatitis or other causes of liver injury have instead found that some bioanalytical methods for the detection of APAP yield high rates of false positives in the presence of high bilirubin levels and thus may have resulted in overestimation of APAP use during acute liver disease in some studies [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Polson et al concluded that false positive acetaminophen tests might result when enzymatic-colorimetric assays are used, typically when bilirubin exceeds 10 mg/dl. 4 Similarly, Bertholf et al selected 12 patients without a history of acetaminophen ingestion with serum bilirubin concentrations ranging from 15-34 mg/dl. They concluded that their data was consistent with bilirubin interference in the enzymatic and / or chromogenic reactions involved in the acetaminophen method, with no detectable acetaminophen levels when total bilirubin was <5 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hullin et al reported high immunoglobulin levels affecting APAP quantification leading to underestimated amounts [11]. The presence of high endogenous bilirubin concentrations was also demonstrated to lead to false positive results [8,12]. Crossreactivity that is difficult to predict is also known to potentially affect immunoassays results [13].…”
Section: Introductionmentioning
confidence: 98%
“…The quantification methods used routinely in clinical chemistry or emergency toxicology are often based on immunoassays detection [8] or GC-MS(/MS) techniques [9,10]. Immunoassays are largely used but suffer from a lack of selectivity.…”
Section: Introductionmentioning
confidence: 99%